Ambroxol hydrochloride spray (Luo Runchang®) in the treatment of acute respiratory infectious diseases: a prospective, multicenter, open label, randomized controlled study - Cheng, Lu; Liu, Min; Wang, Rong; Cao, Sufen; Li, Rui; Su, Bo; Wei, Hongyan; Yang, Haijuan; Hou, Lingyun; Geng, Chunyu; Han, Yuling; Yang, Tianrui (Frontiers in Pediatrics, 2024)
Purpose: Cough and sputum are the most common clinical symptoms of acute respiratory tract infection. Ambroxol is a mucolytic expectorant commonly used in clinical practice. This study aimed to evaluate the efficacy, safety, and compliance of ambroxol hydrochloride spray (Luo Runchang ®) for the treatment of acute respiratory tract diseases in children. Methods: This was a multicenter, open-labeled, randomized controlled study. The experimental group received ambroxol hydrochloride oral sprays, and the control group received ambroxol hydrochloride oral solutions. The primary endpoint was the change in cough symptom scores from baseline. Secondary endpoints include changes in cough severity score, quality of life, adherence, and adverse events. Results: A total of 154 subjects were randomized and included in the analysis. The mean change of total cough symptom score of the spray group at the end of treatment was -4.7(1.54) compared to -4.2(1.62) in the solution group (P=0.0005). The mean change of cough severity score was -5.7(2.09) in the spray group compared to -5.2(2.04) in the solution group (P=0.012). Quality of life scores significantly improved in the spray group (P < 0.0001) compared to the oral solution group. Medication adherence markers were significantly better in the spray group (P < 0.0001). The incidence of adverse events in the experimental group (1.33%) was lower than that in the control group (6.33%), but the difference between the groups was not statistically significant. Conclusion: Ambroxol hydrochloride spray significantly improved cough symptom score, cough severity score, and quality of life score compared to ambroxol hydrochloride oral solution.